Homelessness within Homeland: Oppression of Hazara in Hosseini’s The Kite Runner - Gajamer, Sangita (Khwopa Journal, 2023)
In Khaled Hosseini’s The Kite Runner, I explore the ethnic tension between the Pashtun and Hazara communities and the Pashtun's suppression of the Hazara community. Hosseini advocates for the oppressed Hazara minority in the novel, as a member of the ruling Pashtun community, he unconsciously glorifies his own racial superiority by presenting the Hazara as voiceless and miserable, unable to survive without the aid of the Pashtun community. Regarding Hazaras in the novel, the concept of citizen is not applicable since they are discriminated against and excluded by Sunni extremists in Afghanistan. Sunnis are “privileged,” and this position has created a situation of discrimination and inequality towards the underprivileged Hazaras, and they are denied to have equal rights. Hazaras in Afghanistan are not treated as “citizen subjects,” and they have been living in a stateless condition, full of discrimination, inequality, and mistreatment. To deal with the issues, the internal displacement of Hazara communities and the historical background of refugees in Afghanistan, I have brought the ideas of Derrida, Foucault, Hannah Arendt, Balibar, Hemel, Agamben, Ranciere, as my theoretical tools as well as other references from migration, displacement, and refugee and try to connect the refugee crisis of The Kite Runner in a global spectrum.